Peningkatan Minat In-game Purchase Pada Remaja di Batam Selama Masa Pandemi - Marvin Christian; Jonathan Jonathan; Henry Henry; Ricky Wijaya; Kevin Charles (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The growing number of video game industry has made video game developers to take advantage of the opportunities to develop video games that have interesting gameplay. One being to utilize in-game purchases to create a more engaging experience. Therefore, this study aims to examine the effect of immersion and telepresence on interest in in-game purchase among teenagers in Batam, and to find out the factors to be considered by video game development companies in leveraging their in-game purchase. This research is conducted quantitatively by distributing questionnaires to 200 respondents throughout Batam. The results were analyzed using linear regression method through SPSS. The results showed that immersion did not affect the increase in interest in-game purchase among teenagers in Batam. However, the results showed that telepresence has a significant effect on increasing the interest of teenagers in in-game purchase. It is implied that game development companies should consider telepresence as a factor that promotes in-game purchase in their video games.